ACS management capacity enhancement mechanism in CWMP. Issue 2 (1st January 2014) - Lee, K.M.; Chu, H.; Chu, J.; Lin, Y.; Hsiao, C.; Hou, T.W.
Abstract : The autoconfiguration and management features of the Customer Premises Equipment (CPE) WAN Management Protocol (CWMP) are powerful and have been extensively used by service providers and telecommunication services. The capability of the auto configuration server (ACS) in the CWMP technology is limited by its management structure, the maximum connection and the network bandwidth. Typically, these concerns are solved by adding more ACSs. Nevertheless, the ACS that has stronger management power is pricy too. On the other hand, the computing power of the CPE having lower costs is increasing rapidly. To utilise the benefits of this change, a new design by combining a sub‐ACS concept with a dynamic adaptive multi‐level grouping algorithm mechanism is created, that is to recalculate a healthy rate of the ACS while a new CPE is joining the system. If the healthy rate of the ACS is below the healthy criteria, a new group of CPEs and its corresponding sub‐ACS are built. The newly formed sub‐ACS responds to manage the new group. By leveraging the new model, the management capability of a CWMP system can be raised to 278%. Consequently, the infrastructure of establishing both the cost and the operation cost is reduced, yet the efficiencies of the entire remote management system can be improved.